A Study on Assessment of Pharmacotherapy, Etiology, and Risk Factors in Heart Failure Patients in Tertiary Care Hospital - P, Sajan Francis; M, Abhijna; Kunju, Aksa A; Joseph, Arlin; Tellis, Michelle Petrisha; K, Vinitha; r, Ravikumar (Indian Journal of Pharmacy Practice)
Background: Heart failure is described by the ACC Foundation and AHA as “a complex clinical syndrome resulting from any anatomical or functional impairment of ventricular filling or blood ejection. The main aim was to assess the pharmacotherapy, drug utilization pattern, precipitating factors, and aetiological factors of heart failure. Materials and Methods: The study is a single-centred prospective observational study that was conducted for 6 months. Patients were selected based on study criteria. Results: Out of 155 heart failure, the patient’s most prevalent age group was between 61 and 70 years (33.5%) with a mean of 61.96(±13.72). Out of 155 patients, 86 (55.4%) had a decreased ejection fraction, and the majority of patients were men (53.45%). The most prevalent precipitating variables were found to be anaemia 51(18.68%), hypertension 82(30.03%), and diabetes mellitus 70(25.64%). Cardiomyopathy 70(43.48%) and ischemic heart disease 83(40.88%) were the most often discovered underlying causes in patients with heart failure. The most frequent comorbidities were renal disorders 42(21.53%), hypertension 46(23.58%), and diabetes mellitus 42(23.58%). Around 139(90.25%) prescriptions contained diuretic drugs. Furosemide (69.63%) was the most commonly prescribed diuretic. Followed by antihypertensives 132(85.71%) and digoxin was prescribed to 32 (20.64%) patients. About 36.90% of patients received aspirin and atorvastatin combination drugs. Conclusion: Our study concluded that ischemic heart disease and dilated cardiomyopathy are the core underlying causes of heart failure. Hypertension and diabetes mellitus is considered to be the most common predisposing factors. The most frequent monotherapy prescribed for heart failure includes diuretics, antihypertensives, antiplatelets, and lipid-lowering agents while aspirin and atorvastatin were the most commonly prescribed combination therapy.
Keywords: HF patients; Ejection fraction; Hypertension; Hypernatremia; Diuretics